ATTEMPTED SYNTHESIS OF BIS-SPIROEPOXIDE DITHIANEDIOXIDE - Ritmaleni Ritmaleni; Varinder K. Aggarwal (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
The bis-spiroepoxide dithiane dioxide has been attempted to be synthesised as its role as an intermediate in the synthesis of diaminopimelic acid (DAP). The first method was carried out by reacting the 3-dithiane-2-diethylphosphonate 4 with an aqueous solution of the commercially available glutaraldehide resulting the bis-ketene dithiane dioxide 5. The second alternative method was involving the ozonolysis of cyclopentene 7 in the synthesis of bis-ketene dithiane dioxide 5 in four step reactions which gave moderate to good yield. Unfortunately, epoxidation process for the bis-ketene dithiane dioxide 5 was still unsuccess yet.Key words: synthesis, diaminopimelic acid, bis-spiroepoxide dithiane dioxide